Faktor-Faktor Yang Berhubungan Dengan Peran Keluarga Dalam Pengawasan Menelan Obat Pada Pasien Tuberkulosis Paru - Mardiono, Sasono; Saputra, Andre Utama; Romadhon, Muhammad (JURNAL KESEHATAN TERAPAN, 2023)
Tuberculosis is one of infectious chronic disease which still becomes society healt problem inthe word ,includes indonesia.drinking medicine obedience number of tuberculosis patient in Opi Healt center has not fulfilled the national target yet,and tends to dectease ever year .the medication to Tuberculosis patient can be done using some medicine combination that intended to exaterminate the germ.WHO recommends medication strategy,DOTS.that patient drink medicine supervised by drinking medicine supervisor.the research is aimed to know the relation of DMS (Drinking Medicine Supervisor) to drinking medicine obedience of Tuberculosis. The purpose of this study has been known factors related to the incidence of typoid fever. in Poli Rawat patient can be doneand Inpatient Room Kayuagung Hospital. This research is quantitative using analytical survey methods, and accidental sampling techniques.while the reseach place was conducted in the Opi Palembang health center on agust 21-28,2021.the population in the study was all patient who experienced Tuberculosis 2020some 40 people,and for the sample of 40 respondents. The results of the study were obtained based on the Chi-Square test have a relationship between educationand the role of families inthe supervision of swallowing drugs in the Tuberculosis education with a p-value of 0.001, there is a link between work and the role of families in drug swallowing supervision in high health Tuberculosis patient with a p-value of 0.001, there was a correlation between the level of knowledge was with the role of family supervisory draught swallow drugs on Tuberculosis patent with a p-value of 0.003